Inter-Ethnic Marriage and Partner Satisfaction - Worner, S; Sinning, M (My University, 2010)
This paper investigates immigrant assortative mating and relationship satisfaction. Using a modified random effects ordered probit model, the paper demonstrates that spouses of mixed couples are significantly less satisfied with their partner than nativeonly and foreign-only couples.
Australian National University College of Business and Economics Working Paper
Keywords: Satisfaction -- Relationships; Satisfaction; Families and relationships; Satisfaction; Relationships; Families and relationships